Potentiation of β-Lactams against Methicillin-Resistant Staphylococcus aureus (MRSA) Using Octyl Gallate, a Food-Grade Antioxidant - Migma Dorji Tamang; Junghee Bae; Myungseo Park; Byeonghwa Jeon (MDPI AG, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is resistant to a number of antibiotics of clinical importance and is a serious threat to public health. Since bacteria rapidly develop resistance even to newly discovered antibiotics, this study aimed to develop drug potentiators to enhance the antibacterial activity of existing antibiotics for the control of MRSA. Based on our previous studies, screening of antimicrobial synergy was conducted with gallic acid and its derivatives using checkerboard assays. Antimicrobial synergy was confirmed with MRSA isolates from clinical cases. Combinations of penicillin, ampicillin, and cephalothin with octyl gallate (OG), an antioxidant approved by the US Food and Drug Administration (FDA), consistently exhibited synergistic bacteriostatic and bactericidal activities against MRSA, rendering MRSA sensitive to β-lactams. The fractional inhibitory concentration (FIC) and fractional bactericidal concentration (FBC) indices exhibited that the antimicrobial effects of OG were synergistic. The results of a permeability assay showed that OG significantly increased the permeability of the bacterial cell wall. Despite the intrinsic resistance of MRSA to β-lactams, the findings in this study demonstrated that OG enhanced the activity of β-lactams in MRSA and sensitized MRSA to β-lactams, suggesting that OG can be used as a drug potentiator to control MRSA using existing antibiotics.